PENGAKUAN DAN PERLINDUNGAN HUKUM TERHADAP MASYARAKAT HUKUM ADAT (DALAM PERSPEKTIF NEGARA HUKUM) - SARI, NI LUH ARININGSIH (GANEC SWARA, 2020)
The State of Indonesia as an archipelago with thousands of ethnic groups with a variety of different cultural customs in indigenous groups and local wisdom makes the State of Indonesia famous as a country rich in ethnicisity. The existence of indigenous community in various laws and regulations including the Constitution recognizes the existence of indigenous community and even the constitution mandates separate regulations in the form of laws to protect the existence of them and their customary rights. However, in practice in social life, their existence has not yet received serious protection from the government. This can be seen from the fact that not all regional heads inventoried and made local regulations related to indigenous community and local wisdom in their area and the rights of indigenous community to their customary territories are often disturbed by the rights granted by the laws and regulations made by the State. Whereas the state's recognition of the existence of customary law communities has been regulated in various national laws and regulations even in the Unitary State of the Republic of Indonesia, namely in the 1945 Constitution Article 18B paragraph (2) containing that the State recognizes and respects community units customary law and traditional rights as long as they are still alive and in accordance with the development of society and the principles of the Unitary State of the Republic of Indonesia as stipulated in the law.